Biomassa Sebagai Sumber Energi Alternatif dan Terbarukan Melalui System Literature Review - Prastyo, Hadi; Abil Fadila; Muhammad Farrel Syabena; Umadi, Sarah Sakinah; Andika Yuli Heryanto (Jurnal Informasi, Sains dan Teknologi, 2025)
Biomass as a renewable energy source holds immense potential and is applicable across various industrial sectors, being both renewable and sustainable. Renewable energy derived from biomass is widely recognized as one of the most significant energy alternatives due to its environmental friendliness, as it originates from living organisms and has the capacity and availability to serve as a future energy source. This research aims to identify the development of research on biomass as an energy source, specifically in Indonesia, using the Systematic Literature Review (SLR) technique guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology. SLR, which follows standardized rules for identifying and synthesizing relevant studies, provides a comprehensive understanding of the topic's current knowledge base. Data were collected from journals using the Publish or Perish application; an initial search of the Google Scholar database yielded 1600 articles, which were rigorously screened, resulting in 1508 exclusions and 92 inclusions for thorough analysis. Ultimately, this SLR method effectively demonstrates the development of research concerning biomass as a renewable energy source.